Legal Analysis of Consumer Protection Towards Passenger Safety in Sea Transportation: Research Study at Sekupang Domestic Port, Kepri (International Journal of Education and Literature, 2024)
The background of this research is the high risk of accidents in the marine transportation sector that threatens passenger safety, as well as the need for an in-depth analysis of the effectiveness of existing regulations in protecting consumers. This study aims to find out and analyze the legal regulations for consumer protection for passenger safety in sea transportation, evaluate the implementation of relevant laws and regulations, and analyze consumer protection barriers to passenger safety in sea transportation. The research methods used are normative juridical and empirical sociology. Normative juridical research is carried out by analyzing applicable laws and regulations, including Law Number 17 of 2008 concerning Shipping, Law Number 8 of 1999 concerning Consumer Protection, as well as various technical regulations such as Regulation of the Minister of Transportation Number 45 of 2012 and Government Regulation Number 51 of 2002. An empirical sociological approach is carried out through interviews and direct observation at the Riau Islands Sekupang Domestic Port to understand the implementation of regulations and safety perceptions among passengers and shipping business actors. The results of the study show that the legal regulation of consumer protection is regulated in Law Number 17 of 2008 concerning Shipping, Law Number 8 of 1999 concerning Consumer Protection, as well as various technical regulations such as Regulation of the Minister of Transportation Number 45 of 2012 and Government Regulation Number 51 of 2002, even though safety regulations have been stipulated that consumer protection is still not running optimally. The main obstacles include limited resources, non-compliance of business actors, and inadequate infrastructure. Ineffective supervision and law enforcement are also the main inhibiting factors. To overcome these obstacles, it is recommended to increase resources and facilities, stricter law enforcement, and increase safety awareness and education among passengers and crew. The government also needs to increase investment in port infrastructure and strengthen coordination between relevant agencies.